Return motivated by economic crisis in north america (Tempo e Argumento, 2009)
The formation of a Brazilian migration network from the Governador Valadares region in Brazil to the United States began in the 1960s, and, by the 1980s, it was consolidated. During that period many Brazilian immigrants returned to Brazil, others continued to reside in the United States, while some became transmigrants. In 2007 a different move began. The immigrants, affected by the crisis of the U.S. economy, start to return – and this is the focus of this article. I conducted 398 interviews with Brazilian migrants who returned to Brazil from June, 2007 to December, 2008. Research results show that the majority of Brazilian immigrants were undocumented, lived in the United States between three to five years, and returned because their financial profits did not compensate the risks anymore. About 18% had recently made investments in Brazil that would guarantee their survival; 51% had capital to invest; and 21% did not know how to survive in Brazil, while 28% intended to migrate to Europe.
Keywords: economic crisis; migration; return